Effects of purified anthocyanin supplementation on platelet chemokines in hypocholesterolemic individuals: a randomized controlled trial. Issue 1 (December 2016) - Zhang, Xiandan; Zhu, Yanna; Song, Fenglin; Yao, Yanling; Ya, Fuli; Li, Dan; Ling, Wenhua; Yang, Yan
Abstract Background It is becoming increasingly evident that platelet chemokines are involved in distinct aspects of atherosclerosis. The aim of this study was to examine the effects of long-term supplementation with purified anthocyanins on platelet chemokines in hypercholesterolemic individuals and to identify correlations of decreased platelet chemokine levels with serum lipid and inflammatory marker levels. Methods A total of 146 hypercholesterolemic individuals were recruited and treated with 320 mg of purified anthocyanins (n  = 73) or a placebo (n  = 73) daily for 24 weeks in this randomized, double-blind, placebo-controlled trial. Results Anthocyanin supplementation for 24 weeks significantly decreased the plasma CXCL7 (–12.32% vs. 4.22%, P  = 0.001), CXCL5 (–9.95% vs. 1.93%, P  = 0.011), CXCL8 (–6.07% vs. 0.66%, P  = 0.004), CXCL12 (–8.11% vs. 5.43%, P  = 0.023) and CCL2 levels (–11.63% vs. 12.84%, P  = 0.001) compared with the placebo. Interestingly, the decreases in the CXCL7 and CCL2 levels were both positively correlated with the decreases in the serum low-density lipoprotein-cholesterol (LDL-C), high-sensitivity C-reactive protein (hsCRP) and interleukin-1β (IL-1β) levels after anthocyanin supplementation for 24 weeks. The decrease in the CXCL8 level was negatively correlated with the increase in the how-density lipoprotein-cholesterol (HDL-C) level and was positively correlated with the decrease in the soluble P-selectin (sP-selectin) level in the anthocyanin group. In addition, a positive correlation was observed between the decreases in the CXCL12 and tumornecrosis factor-α (TNF-α) levels after anthocyanin supplementation. However, the plasma CXCL4L1, CXCL1, macrophage migration inhibitory factor (MIF) and human plasminogen activator inhibitor 1 (PAI-1) levels did not significantly change following anthocyanin supplementation. Conclusions The present study supports the notion that platelet chemokines are promising targets of anthocyanins in the prevention of atherosclerosis. Trial registration ChiCTR-TRC-08000240 . Registered: 10 December 2008.